(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The interest in sustainable organizational performance has increased strongly in the last decade. With the rising macroeconomic pressure and unforeseen circumstances such as global pandemic, an increased number of economies battle to ensure prosperity, performance, and target trans-formation. The aim of this study is to spot trends and developments on sustainable organizational performance observed in the academia for the last decade. More precisely, main sources of publications as well as biases within geographical, citation, authorship and thematic dimensions are to be identified. To achieve this aim, a qualitative study based on bibliometric analysis has been performed. In total, 1286 relevant articles were retrieved for the last decade that examined sustainable organizational performance, however none of them has implemented a systematic literature review and bibliometric analysis and elaborate on progress within academic research. The bibliometric analysis within this study is based on a literature review of publications obtained from Scopus using an inclusive search strategy. In addition, the visualization of the data was carried out with the use of Bibliometrix and VOSviewer. The article strives to contribute to the research on sustainable organizational performance, while performing keywords and co-occurrence analysis. It further defines top productive authors, structure of the research topic in the journals and countries. In addition to that, Lotka analysis has been performed to understand the interactions and structure of publications of the subject area. The importance of the organizational framework, management and governance were identified as main keywords underlying once again that functional framework provides structure and hierarchy the entity may build on, while effective management ensures the utilization of resources within the established framework. Oversight, in turn, is organized by governance that guides both the framework and management practices. The study comes with the conclusion and recommendations for both business and academia. ;